1998
DOI: 10.1111/j.1540-5915.1998.tb01350.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Metamodel for Response‐Time Planning*

Abstract: Field service management continues to be a major challenge for many service organizations as companies are required to provide more service with less resources. Especially in information intense environments, short response times for service calls are essential to avoid disruptions to a business office or production facility. Managers must regularly assess their manpower needs, and ensure that their allocation and operational decisions lead to the best service at the lowest cost.Xerox Corporation provides copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…New hires, training, skill, contracts, customer satisfaction, service types, product types, shifts, call arrival rates, job completion probability, interruptions, travel time distribution, skill-based process times, dispatching algorithms Watson et al 9 Staffing and response time planning…”
Section: Simulation Of Field Service Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…New hires, training, skill, contracts, customer satisfaction, service types, product types, shifts, call arrival rates, job completion probability, interruptions, travel time distribution, skill-based process times, dispatching algorithms Watson et al 9 Staffing and response time planning…”
Section: Simulation Of Field Service Networkmentioning
confidence: 99%
“…2,8 Today, most methods used in field service network (FSN) planning in practice are 'outdated and overly simplistic'. 9,10 Similar to the supply chain area years ago, decision makers are missing ''a comprehensive methodology and engineering design method that allows them to rapidly prototype and evaluate several [. ] configurations [.…”
Section: Introductionmentioning
confidence: 99%
“…E, is a random error term composed of the error of any excluded or unidentified input factors and the error of fitting the polynomial. This latter component is assumed to distribute according to N (0, 0); Regression metamodels have been applied to manufacturing and operations management [17,25,261 and Sartori and Smith [21] extended their use to the field of engineering economy. They employed experimental design and regression metamodels in the sensitivity analysis of capital investment decisions and showed that this approach provided more insight than traditional sensitivity analysis.…”
Section: The Conceptmentioning
confidence: 99%
“…When the response time exceeds a predefined value, assistance is requested from service engineers from other territories. Sometimes, a ''floater'' field engineer is used to provide assistance across territories (Watson et al, 1998). Other examples include call centers where the number of customer service representatives is varied depending on the call arrival rates, and communication networks where the number of network connections is varied depending on the traffic congestion.…”
Section: Introductionmentioning
confidence: 99%